1983
DOI: 10.1149/1.2119851
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Raman Spectroscopic Studies of the Rechargeable Low Temperature Molten Salt Cell: Na/Beta″‐Alumina/S(IV) in

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
1987
1987

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…As expected from the ratio of the n-values, the ratio of the number of coulombs in the first to the second plateau was found to be ,~2, indicating the formation of sulfur in the --2 state. Recent Raman spectroscopic studies (10,11) have shown that sulfide in acidic melts is present as oligomeric A1SC1. The overall reaction corresponding to the second discharge plateau can be written in simplified form as 2Na…”
Section: Resultsmentioning
confidence: 99%
“…As expected from the ratio of the n-values, the ratio of the number of coulombs in the first to the second plateau was found to be ,~2, indicating the formation of sulfur in the --2 state. Recent Raman spectroscopic studies (10,11) have shown that sulfide in acidic melts is present as oligomeric A1SC1. The overall reaction corresponding to the second discharge plateau can be written in simplified form as 2Na…”
Section: Resultsmentioning
confidence: 99%
“…Open-circuit voltage for this step in the basic melt is 2.75V. Chemistry and electrochemistry of several sulfur species in A1CI:~-NaC1 melts of different compositions have been studied in our group (7)(8)(9)(10)(11)(12) and elsewhere (13)(14)(15)(16). As is apparent from Eq.…”
Section: Discharge 2na + S + A1c13 ~ ~ A1sc1 + 2nac1 [2] Chargementioning
confidence: 99%
“…[1], the modified Lewis acidity of the positive electrode mix decreases in the course of discharge. Since SCI:~ § is stable only in acidic melts (mole percent (m/o) of A1CI:~ > 50) (10), the positive electrode mix must remain acidic as long as some tetravalent sulfur is present in the melt (11). However, the positive electrode mix can become basic when the formal oxidation state of sulfur (FOXS) is + 1 or less.…”
Section: Discharge 2na + S + A1c13 ~ ~ A1sc1 + 2nac1 [2] Chargementioning
confidence: 99%